2022
DOI: 10.1049/hve2.12200
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of the potential of superhydrophobic surfaces in reducing audible noise on HVAC overhead line conductors

Abstract: Overhead line conductors can generate audible noise across a wide frequency spectrum as a result of elevated electric fields at the conductor surface. Such fields are enhanced by the presence of surface defects, insects, water drops and pollution. Within this paper, the impact of a superhydrophobic coating on the audible noise produced by an overhead line conductor is examined. Noise levels from a conductor coated with a superhydrophobic coating were compared to those from a bare conductor in a semi‐anechoic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Yi et al (2016) found that the DC corona inception voltage increases with the thickness of the RTV coating on the aluminum conductor steel reinforced (ACSR). Zhang et al (2019Zhang et al ( , 2022 applied a commercial superhydrophobic coating on ACSR, the SCA was 162.4 °. The application of the superhydrophobic coating greatly reduces the quantity of droplets on the ACSR and reduces the electric field distortion generated by the tip of the water droplet.…”
Section: Coatings Aim At Conductors Coronamentioning
confidence: 99%
See 1 more Smart Citation
“…Yi et al (2016) found that the DC corona inception voltage increases with the thickness of the RTV coating on the aluminum conductor steel reinforced (ACSR). Zhang et al (2019Zhang et al ( , 2022 applied a commercial superhydrophobic coating on ACSR, the SCA was 162.4 °. The application of the superhydrophobic coating greatly reduces the quantity of droplets on the ACSR and reduces the electric field distortion generated by the tip of the water droplet.…”
Section: Coatings Aim At Conductors Coronamentioning
confidence: 99%
“…The images captured by the UV camera of (A) uncoated conductors, (B) coated conductors (Zhang et al, 2022). Measured noise levels (dB above background) as a function of electric field and frequency with continuous water spray on (C) uncoated conductors, (D) coated conductors (Zhang et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…As it is known, the protective coatings under development for overhead line wires can improve or deteriorate the bandwidth of high-frequency communication channels, as well as affect the electrical characteristics of the conductor. Therefore, we experimentally determined the change of the studied characteristics from the application method and the number of layers of oxide nanostructured coating [35][36][37].…”
Section: Investigation Of the Effect Of A Nanostructured Coating On A...mentioning
confidence: 99%
“…Therefore, a semianechoic chamber in the high voltage lab of the University of Manchester was built to reduce baseline noise levels. A comparison of untreated conductors and conductors with a superhydrophobic coating under a continuous water spray and an AC voltage was then carried out and reported in our previous paper [18]. It was shown that the 2f hum noise and overall sound pressure levels can both be reduced with a superhydrophobic coating.…”
Section: Introductionmentioning
confidence: 98%
“…It was shown that the 2f hum noise and overall sound pressure levels can both be reduced with a superhydrophobic coating. A comparison of the droplet distributions gave some evidence for the cause of noise reduction [18].…”
Section: Introductionmentioning
confidence: 99%